The turnover of health professionals in the Family Health Strategy in the City of Rio Grande do Piauí-PI (Research, Society and Development, 2021)
This study analyzes the turnover of health professionals in the Family Health Strategy in the city of Rio Grande do Piauí. It seeks to verify the influence of this phenomenon on the team members and on the quality of health services provided to the population. This is a study with a qualitative approach, in which an interview with the research subjects was applied and the annual turnover index and average was analyzed, in addition to the types of bonds in the municipality's ESF contracts. The results show an unstable turnover rate, being high in certain periods, in addition, instability also predominates in the form of hiring professionals, with 75% for a fixed period. The analysis of the interviews indicates that the dissatisfaction of these professionals is the main cause of turnover, due to the authoritarian management style, poor working conditions, structural problems, work overload, absence of labor laws that bring security to the server and, being the main problem, the fact that professionals live in other municipalities. This context demonstrates the need to seek improvements in relation to leadership, working conditions, the way of managing public resources, so that the practices of the ESF are carried out in their entirety.